2022
DOI: 10.1007/s40262-022-01150-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics of Milvexian in Participants with Normal Renal Function and Participants with Moderate or Severe Renal Impairment

Abstract: Objective The aim of this study was to assess the effect of moderate or severe renal impairment on the pharmacokinetic (PK) properties of milvexian. Methods This open-label, parallel-group study assessed the PK, safety, and tolerability of a single oral 60 mg dose of milvexian in participants with normal renal function ( n = 8; estimated glomerular filtration rate [eGFR] ≥ 90 mL/min/1.73 m 2 ) and participants with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Compared with those with healthy renal function (13.8 h), the half-life was longer in subjects with moderate (18.0 h) or serious (17.7 h) renal disorders. This showed that Milvexian is safe and well tolerated in people with renal dysfunction [ 37 ]. A dose-exploration trial of Milvexian examined the tolerability, safety, PD and PK characteristics of sequential single incremental doses (SADs) and multiple incremental doses (MADs).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with those with healthy renal function (13.8 h), the half-life was longer in subjects with moderate (18.0 h) or serious (17.7 h) renal disorders. This showed that Milvexian is safe and well tolerated in people with renal dysfunction [ 37 ]. A dose-exploration trial of Milvexian examined the tolerability, safety, PD and PK characteristics of sequential single incremental doses (SADs) and multiple incremental doses (MADs).…”
Section: Resultsmentioning
confidence: 99%
“…The total exposure to milvexian, after a single oral 60 mg dose, was 41% and 54% greater in participants with eGFR values of 30 and 15 mL/min/1.73 m 2 , respectively, than in subjects with normal renal function. The median time to maximum concentration (T max ) was similar for the three groups (4.5–5.0 h), and the half-life increased for participants with moderate (18.0 h) or severe (17.7 h) renal impairment compared with those with normal renal function (13.8 h) [ 43 ]. Thus, according to the low renal excretion, a single dose of milvexian 60 mg was safe and well tolerated in participants with moderate or severe renal impairment [ 43 ].…”
Section: Doac and Small Drug Molecules Anti Fxia: Potential Differenc...mentioning
confidence: 99%
“…The median time to maximum concentration (T max ) was similar for the three groups (4.5–5.0 h), and the half-life increased for participants with moderate (18.0 h) or severe (17.7 h) renal impairment compared with those with normal renal function (13.8 h) [ 43 ]. Thus, according to the low renal excretion, a single dose of milvexian 60 mg was safe and well tolerated in participants with moderate or severe renal impairment [ 43 ].…”
Section: Doac and Small Drug Molecules Anti Fxia: Potential Differenc...mentioning
confidence: 99%
See 1 more Smart Citation
“… 91 Higher doses (200 or 500 mg) appeared to prolong the aPTT for over 24 h. 91 The half-life of milvexian was slightly longer (∼18 h) in patients with moderate (eGFR from ≥30 to ≤59 mL/min/1.73 m 2 ) and severe (eGFR < 30 mL/min/1.73 m 2 ) renal impairment. 92 Milvexian is a substrate for CYP3A4 ( Table 1 ) and P-glycoprotein (P-gp). 93 , 94 Milvexian exposure was moderately increased following concomitant use with multiple doses of itraconazole (a strong CYP3A4 and P-gp inhibitor) but was slightly increased following multiple doses of diltiazem (a moderate CYP3A4 inhibitor).…”
Section: Milvexianmentioning
confidence: 99%